Investor Sentiment and Option Prices - Han, Bing (Review of Financial Studies, 2008)
This paper examines whether investor sentiment about the stock market affects prices of the S&P 500 options. The findings reveal that the index option volatility smile is steeper (flatter) and the risk-neutral skewness of monthly index return is more (less) negative when market sentiment becomes more bearish (bullish). These significant relations are robust and become stronger when there are more impediments to arbitrage in index options. They cannot be explained by rational perfect-market-based option pricing models. Changes in investor sentiment help explain time variation in the slope of index option smile and risk-neutral skewness beyond factors suggested by the current models. The Author 2007. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For permissions, please email: journals.permissions@oxfordjournals.org, Oxford University Press.